STUDY OF ENHANCING STUDENT’S LEARNING ACHIEVEMENT BY THE USE OF PQ4R (PREVIEW, QUESTION, READ, REFLECT, RECITE,REVIEW) ELABORATION STRATEGIES METHOD IN THE ISLAMIC RELIGIOUS STUDY - Feisal Ghozaly (Widyariset, 2011)
In general, teachers used to teach the Islamic Religious Education (PAI) in the conventional method of learning. This research aims to determine whether the use of PQ4R elaboration strategies methods in learning can enhance students’ learning achievement systematically in SMP Negeri 15 Mataram. This research used a descriptive approach seeking to examine moredeeply the use of PQ4R elaboration strategies methods. The results showed that the average score of the subjects increased ranging from 74.91 on the precondition capability to 82.08 on the first act, and increased to 85.25 in the second act, and rose again to 87.20 in the third act. Thus, PAI learning using PQ4R elaboration strategies methods are proven to improve student achievement.